2014
DOI: 10.1099/ijs.0.063875-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of Propionispira arcuata sp. nov., isolated from a methanogenic reactor of cattle waste, reclassification of Zymophilus raffinosivorans and Zymophilus paucivorans as Propionispira raffinosivorans comb. nov. and Propionispira paucivorans comb. nov. and emended description of the genus Propionispira

Abstract: A strictly anaerobic bacterial strain, WK011T, was isolated from a methanogenic reactor treating waste from cattle farms. The cells stained Gram-negative and were curved rods with a polar or subpolar flagellum. Spore formation was not observed. The optimum temperature for growth was 35 °C and the optimum pH was 6.7. Tests for oxidase, catalase and nitrate-reduction activities were negative. Hydrogen sulfide was produced. The strain fermented carbohydrates and produced acetate and propionate as major fermentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Strains FH052 T and SN021 T were isolated by the anaerobic roll-tube method (Holdeman et al, 1977) from a methanogenic reactor treating waste collected from cattle farms (housing up to 1000 cattle in total) in Betsukai-machi, Hokkaido, Japan, as described previously (Nishiyama et al, 2009;Ueki et al, 2009Ueki et al, , 2014Ueki et al, , 2015. Strain FH052 T was from digester fluid without plant residue or other solid material and strain SN021…”
mentioning
confidence: 99%
“…Strains FH052 T and SN021 T were isolated by the anaerobic roll-tube method (Holdeman et al, 1977) from a methanogenic reactor treating waste collected from cattle farms (housing up to 1000 cattle in total) in Betsukai-machi, Hokkaido, Japan, as described previously (Nishiyama et al, 2009;Ueki et al, 2009Ueki et al, , 2014Ueki et al, , 2015. Strain FH052 T was from digester fluid without plant residue or other solid material and strain SN021…”
mentioning
confidence: 99%
“…The sediment prior to glucose amendment comprised a varied microbial community with 70 % identifiable species from the Acidobacteria, Gammaproeobacteria and Alphaproteobacteria classes ( Figure 5; Thorpe et al, 2012). (Shelobolina et al, 2007;Spring et al, 2003;Schlink, 1984, Liu et al, 2014Ueki et al, 2014;Fischer-Romero et al, 1996;Keis et al, 2001;Jung et al, 2010;Kwon et al, 2008;Kim et al, 2011;Lee et al, 2007). Three samples were taken at regular intervals up to the column, and analysis confirmed a similar microbial community over the 16 cm of sediment ( Figure 5).…”
Section: Microbial Community Characterisationmentioning
confidence: 90%
“…The genus Zymophilus with two brewery-associated species, that is, Zymophilus paucivorans ('user of a few substrates') and Zymophilus raffinosivorans ('raffinose devouring') (Schleifer et al, 1990) was recently combined with the genus Propionispira as they were shown to have a common ancestor (Ueki et al, 2014). In addition to Propionispira paucivorans and Propionispira raffinosivorans, this genus includes Propionispira arboris (Schink, Thompson, & Zeikus, 1982) from wetwoods of living trees (Schink et al, 1982) and Propionispira arcuata (Ueki et al, 2014) from methanogenic cattle waste.…”
Section: Selenomas and Propionispira (Zymophilus)mentioning
confidence: 99%
“…S. lacticifex utilizes a wide range of carbon sources, including arabinose, cellobiose, glucose, lactic acid and maltose (Schleifer et al, 1990). P. raffinosivorans uses a greater variety of carbon substrates compared to P. paucivorans (Schleifer et al, 1990;Ueki et al, 2014). P. raffinosivorans uses a greater variety of carbon substrates compared to P. paucivorans (Schleifer et al, 1990;Ueki et al, 2014).…”
Section: Selenomonas and Propionispiramentioning
confidence: 99%
See 1 more Smart Citation